Предмет: Алгебра,
автор: 40Alina40
Помогите решить пример нижний2 строчка
Приложения:

Ответы
Автор ответа:
0
2(x+3)(x+7) - 2x(x-2) = (x-2)(x+3)
2(x²+7x+3x+21) - (2x²-4x) = x²-2x+3x-6
2x²+14x+6x+42-2x²+4x-x²+2x-3x+6 = 0
-x²+23x+48 = 0
x²-23x-48 = 0
D = 529 - 4*(-48) = 721
√D = √721
x₁ = (23-√721)/2
x₂ = (23+√721)/2
2(x²+7x+3x+21) - (2x²-4x) = x²-2x+3x-6
2x²+14x+6x+42-2x²+4x-x²+2x-3x+6 = 0
-x²+23x+48 = 0
x²-23x-48 = 0
D = 529 - 4*(-48) = 721
√D = √721
x₁ = (23-√721)/2
x₂ = (23+√721)/2
Похожие вопросы
Предмет: История,
автор: maisonshow11
Предмет: Математика,
автор: 5E85skola
Предмет: Математика,
автор: brayanaldairmosqueir
Предмет: Математика,
автор: настя4862